Expression Pattern of Seminal Plasma Extracellular Vesicle Small RNAs in Boar Semen - Xu, Zhiqian; Xie, Yanshe; Zhou, Chen; Hu, Qun; Gu, Ting; Yang, Jie; Zheng, Enqin; Huang, Sixiu; Xu, Zheng; Cai, Gengyuan; Liu, Dewu; Wu, Zhenfang; et al. (Frontiers in Veterinary Science, 2020)
Extracellular vesicles (EVs) regulate multiple physiological processes. Seminal plasma contains numerous EVs that may deliver functional molecules such as small RNAs (sRNAs) to the sperm. However, the RNA profiles in the boar seminal plasma extracellular vesicles (SP-EVs) and its function have not been characterized. The aim of this study was to characterize the functions and sRNA profiles in the boar SP-EVs using deep sequencing technology. Briefly, boar SP-EVs were isolated by differential ultracentrifugation and confirmed with a transmission electron microscope (TEM), nanoparticle tracking analysis (NTA), and Western blot. The isolated boar SP-EVs contained numerous and diverse sRNA families, including microRNAs (miRNAs, 9.45% of the total reads), PIWI-interacting RNAs (piRNAs, 15.25% of the total reads), messenger RNA fragments (mRNA, 25.30% of the total reads), and tRNA-derived small RNAs (tsRNA, 0.01% of the total reads). A total of 288 known miRNAs, 37 novel miRNA, and 19,749 piRNAs were identified in boar SP-EVs. The identified ssc-miR-21-5p may confer negative effects on sperm fertility based on a dual-luciferase reporter experiment. This study therefore provides an effective method to isolate SP-EVs and characterizes the sRNA profile.